PatchWork: A visual programming language and some musical applications - Laurson, Mikael (Helsinki Sibelius Academy, 1996)
The title of this book is PatchWork: A Visual Programming Language and Some Musical Applications and it was written by Mikael Laurson. This edition of PatchWork: A Visual Programming Language and Some Musical Applications is in a Book format. This books publish date is January 1, 1996. It was published by Sibelius Academy and has 313 pages in the book.